Effect of different surfactants on photocatalytic performances of small molecule acceptors - Dey, Mousumi (My University, 2022)
Small molecule acceptor, ITIC has been functionalized with seven different surfactants including PEG and TEBS as anionic surfactants, Triton X 100 as neutral surfactant and ABA, CTAB, CTAC and OEG as cationic surfactants and have been assessed for visible-light-driven hydrogen evolution. All the samples synthesized via the modified nano-precipitation method have been investigated using cryogenic transmission electron microscopy (cryo-TEM). Sizes of the nanoparticles with various surfactants were very small, around 10 nm, in order to diminish the issue of short exciton diffusion path length in organic semiconductors. Cryo-TEM revealed layered crystalline structures of some of the particles associated with high photocatalytic efficiency. Crystallinity has also been confirmed using the powder X-ray diffraction technique. The H and J aggregation peak of the samples have slightly varied depending on surfactants. Therefore, the overall steady-state absorbance range of the samples varied. Despite having similar absorbance, the photoluminescence of the samples largely varied. The quantum yield (QY) values nicely match the photocatalytic performances of the samples with few exceptions. Ascorbic acid and platinum have been used as sacrificial electron donors and co-catalyst respectively to drive the photocatalytic reactions. Time-correlated single photon counting (TCSPC) measurements showed efficient quenching of ITIC nanoparticles capped with PEG, TEBS and CTAB with increasing amounts of ascorbic acid. ITIC surrounded by cationic ABA surfactant has the highest EQE value of 3.2 % at around 650 nm while the highest EQE value of ITIC surrounded by anionic surfactant PEG is 1.8 % at 600 nm.